EDUCAÇÃO RURAL NO NORDESTE: A AÇÃO PLANEJADA DO ESTADO* - Casimiro, Liana Maria Carleial de; Barbosa, Maria Cira de Melo Jorge; Carvalho, Rejane Vasconcelos Accioly (Revista Econômica do Nordeste, 1987)
ACERVO HISTORICO